Development Of A Strategy For The Development Of Physical Culture - Abbasov Bakhadir Asatillayevich (Euro Asian Journal Publishing, 2024)
The program-oriented approach to strategic planning is one of the types of strategic planning, which is based on the orientation of activities to achieve previously set goals. Any method of strategic planning is aimed at achieving certain goals
Keywords: physical culture; program-oriented approach; strategic planning